Karakteristik Vegetasi dan Tanah Hutan Pasca Kebakaran di Gunung Lawu, BKPH Lawu Selatan, KPH Lawu Ds : Vegetation and Soil Characteristics of Post-Fire Forest in Mount Lawu, BKPH Lawu Selatan, KPH Lawu Ds - Irwansyah, Muh Yosrilrafiq; Istomo, Istomo; Syaufina, Lailan (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Forest fire constitutes a major ecological disturbance that induces substantial alterations in ecosystem structure and function, particularly affecting vegetation and soil properties. The Mount Lawu forest, situated within the management unit of BKPH Lawu Selatan, KPH Lawu Ds, has undergone multiple fire events over the past two decades. This study aims to examine characteristics across distinct successional stages, assess soil physicochemical attributes, and identify potential pioneer species capable of adapting to post-fire environments. The investigation was conducted across three successional stages represented by shrubland (burned in 2019), young secondary forest (burned in 2015), and old secondary forest (burned in 2002). Vegetation sampling employed nested plot design, while soil analysis included measurements of pH, organic carbon, total nitrogen, carbon-to-nitrogen ratio, cation exchange capacity, base saturation, and bulk density. The findings reveal successional shifts in species dominance from Imperata cylindrica and Schima wallichii in early stages to Lithocarpus sundaicus in mature forest stands. The assessment of physical and chemical soil properties showed variable results. Biomass accumulation increased along the successional gradient, indicating enhanced ecosystem development. Soil variables exhibited patterns in relation to vegetation structure and biomass.